PENENTUAN REMAINING LIFETIME NET GAS WASH COLUMN BERBASIS LAJU KOROSI INTERNAL DI HYDROCRACKING TREATMENT UNIT PLANT 5 - Risna, Risna; Siwi, Riedel Tryxie; Manik, Nijusiho; Oktafiani, Fitri (PETROGAS: Journal of Energy and Technology, 2024)
Corrosion on the internal equipment of the Net Gas Wash Column is the thinning of the material which, if prevention or control is not carried out, will cause damage or leaks to the equipment. Internal corrosion of equipment such as Net gas wash columns is a common problem in industries that use chemical processes or gas processing. Corrosion occurs when metal materials react with the surrounding environment, such as gases involved in the process, moisture, or other chemicals. Several factors that can cause internal corrosion of equipment such as the Net Gas Wash Column include environmental conditions, material properties, temperature and pressure and the presence of water or humidity. This research aims to determine the corrosion conditions that occur, the impact of corrosion rate, thickness thinning, and the relationship between corrosion rate and remaining lifetime. This research uses a non-destructive testing method, namely the Ultrasonic Test. The results of the analysis and calculations were obtained for the corrosion rate that occurred on the Net Gas Wash Column tool, namely shell 0.11 mm/year and head 0.3 mm/year which was caused by temperature and working flow rate. The direct impact of corrosion is equipment damage and the indirect impact is the costs incurred to replace the equipment. The remaining lifetime for the shell and head is 69 years and 40 years. When the remaining lifetime decreases, the depletion caused by the H2S compound and the corrosion rate will increase immediately. From the results of this research, the relationship between the causes, impacts and corrosion rates on the remaining lifetime of the Net Gas Wash Column equipment can be identified and analyzed.